Improving Financial Literacy and the Accuracy of Financial Statement Preparation Among Accounting Personnel and Stakeholders - Fardinant Adhitama; Nur Khamisah; Asfeni Nurullah; Nilam Kesuma; Ina Masruroh; Ahmad Fikriyansyah; Muthi'a Handayani; Deta Trinalti Oktavia (PT. Altaf Publishing Corp, 2025)
Understanding and analyzing financial statements is an essential skill for stakeholders, particularly for managers and accounting staff in a business or company. This community service activity was carried out as an effort to improve financial literacy comprehension among accounting staff and stakeholders. The activity was conducted through a discussion-based method that delivered material on financial literacy and the preparation of financial statements. This program was attended by 30 accounting staff and stakeholders. As a result of this activity, participants gained a deeper understanding of the importance of accurately and thoroughly interpreting financial statement information, as it significantly impacts future decision-making. Overall, a solid grasp of financial statement information and its preparation enables stakeholders to participate more effectively in the management, supervision, and decision-making processes related to the company.